A Laboratory study of laterite soil mix with usable cooking oil under unsoaked and soaked condition / Abdul Samad Abdul Rahman and Lokman Nur Hakim Zahari - Abdul Rahman, Abdul Samad; Zahari, Lokman Nur Hakim (2012)
@owadays, peoples are more concern about the environment impact assessment towards sustainable development. For that reason, this research is focusing on the effect of the usable daily cooking oils which easily thrown into the soil in the backyard. Furthermore, the stabilization of a foundation in a building mainly depends on the shear strength of soil especially when it's been soaked into the water for a long period of time. Due to that, the mixing of oil with water in the soil may lead to reduction in shear strength and thus will lead to failure in a foundation of structures. A studied were carried out to investigate the effect of mixing samples with usable cooking oil with 3% and 5% into the laterite soil under the condition of unsoaked and soaked for 14 days using multistage triaxial consolidated drained test. From the results, it's show that there are significant reduction in shear strength for control samples and with the mixing of 3% and 5% oil for unsoaked and soaked condition in 14 days. For control sample under unsoaked condition compare to the sample that mix with 3% and 5% of usable cooking oil under the same condition, about 6° of effective friction angle were deduced. Meanwhile for control sample that been soaking compare to 3% mixing, the shear strength were deduced about 6° and for 5% mixing, the shear strength was 9°.In the end, results show that reduction in shear strength will continuously decreased with the increase of the quantities of usable cooking oil and thus will reflect towards the failure of a foundation.